Contribution to the knowledge of the Slovenian Alticinae fauna (Coleoptera: Chrysomelidae) - Malinka, Zdeněk (Acta entomologica slovenica (Ljubljana), 2010)
Additional informations on 48 species of Alticinae (Coleoptera: Chrysomelidae) and its localities in Slovenia are given as a follow-up to the first contribution of the Material for the beetle (Coleoptera) fauna in Slovenia. The recent occurrence of Longitarsus languidus Kutschera, 1863 in Slovenia and L. minusculus (Foudras, 1860) in west part of the country is confirmed. The second recent evidence of L. noricus Leonardi, 1976 and the third recent evidence of Apteropeda orbiculata (Marsham, 1802) in Slovenia are given.
Keywords: entomologija; favna; hrošči; Slovenia; Slovenija; Žuželke